Collaborative Governance in Minimizing the Covid-19 Pandemic in North Aceh Regency - Arinanda, Arinanda; Aiyub, Aiyub; Aisyah, Ti (LPPM Universitas Malikussaleh, 2022)
This study examines the dimensions of Collaborative Governance in minimizing the Covid-19 pandemic. This research uses a qualitative approach with data collection techniques through interviews, observations, and documentation. While the data analysis technique used is an interactive analysis model. The results showed that: 1) Collaborative Governance like Minimizing the Covid-19 Pandemic has not been fully implemented. 2) lack of community participation in health protocols. 3) violation of commitments. 4) the obstacle to minimizing the Covid-19 pandemic is in the factor of collaboration between the government and the private sector and the public which has not been open to the public.